Hydrogen enriched saline alleviates morphine tolerance via inhibiting neuroinflammation, GLT-1, GS nitration and NMDA receptor trafficking and functioning in the spinal cord of rats. (11th June 2021) - Li, Qing; Zhang, Haifang; Jia, Zhen; Zhang, Linlin; Li, Yize; Xu, Rubin; Wang, Chunyan; Yu, Yonghao
Highlights: Neuroinflammation and dysfunction of the central glutamatergic system (such as nitration of glutamate transporter) are involved in morphine tolerance. Hydrogen enriched saline (HS) decreased pro-inflammatory cytokine expressions and attenuated astrocyte activation induced by repeated morphine administration. HS inhibited morphine tolerance probably through decreasing the nitration of glutamate transporter-1(GLT-1) and glutamine synthetase (GS). HS prevents morphine tolerance via inhibiting the total expression and membrane trafficking of N-methyl-d -aspartic acid (NMDA) receptor. Abstract: The development and maintenance of morphine tolerance showed association with neuroinflammation and dysfunction of central glutamatergic system (such as nitration of glutamate transporter). Recent evidence indicated that hydrogen could reduce the levels of neuroinflammation and oxidative stress, but its role in morphine tolerance has not been studied. The rats were intrathecally administered with morphine (10 μg/10 μL each time, twice/day for 5 days). Hydrogen enriched saline (HS) or saline was given intraperitoneally at 1, 3 and 10 mL/kg for 10 min before each dose of morphine administration. The tail-flick latency, mechanical threshold and thermal latency were assessed one day (baseline) before and daily for up to 5 days during morphine injection. The pro-inflammatory cytokine expressions [tumor necrosis factor-alpha (TNF-α), interleukin-1β (IL-1β), IL-6)] (by western blotting), astrocyte activation (by immunofluorescence and western blotting), and nitration of glutamate transporter-1 (GLT-1) and glutamine synthetase (GS) (by immunoprecipitation), membrane and total expression of N-methyl-d -aspartic acid (NMDA) receptor NR1 and NR2B subunits were carried out in the spinal dorsal horns. Chronic morphine administration induced antinociceptive tolerance, and together led to increased TNF-α, IL-1β and IL-6 expression, astrocyte activation, GLT-1 and GS nitration, increased membrane and total NR1, NR2B expression. Injection of HS attenuated morphine tolerance in a dose-dependent manner, decreased proinflammatory cytokine expression, inhibited astrocyte activation, decreased GLT-1 and GS nitration, and inhibited membrane trafficking of NMDA receptor. Our result showed that hydrogen pretreatment prevented morphine tolerance by reducing neuroinflammation, GLT-1, GS nitration, NMDA receptor trafficking in the spinal dorsal horn. Pretreatment with hydrogen might be considered as a novel therapeutic strategy for the prevention of morphine tolerance.